GIS from a computer science perspective. - Trinidad, Gerardo (Philippine Computing Journal)
Is GIS a tool or a science? This is a question the author would like to discuss in this paper. The question is clearly important in operations of academic institution that need to distinguish between GIS as a tool to be taught at the undergraduate level, or a science and thus a legitimate research specialty of faculty and graduate students. Is GIS a tool, involving the use of a particular class of software and associated hardware? Is GIS a tool making endeavour to advance its capability? Is it a science concern about fundamental issues?